Peningkatan Konsep Diri Mahasiswa melalui Komunikasi Interpersonal Pembimbing Akademik - Sari, Hijrayanti (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2017)
The advanced transformation of the era and technology gives influence to human personality today. Specifically to the students which are still in the process ofpersonality development. By the advanced transformation, the competitive environment causes confusion and future disorientation to the students with theirsurroundings. Any behavior is influenced by the self-concept. The self concept is formed through the environment either it is the family, friends, books, or other things seen and listened. The objective of the study is to explain the improvement of the students’ self-concept through the interpersonal effective communicative approach via the supervisors.